Role of dietary fiber in promoting immune health—An EAACI position paper - Venter, Carina; Meyer, Rosan W.; Greenhawt, Matthew; Pali‐Schöll, Isabella; Nwaru, Bright; Roduit, Caroline; Untersmayr, Eva; Adel‐Patient, Karine; Agache, Ioana; Agostoni, Carlo; Akdis, Cezmi A.; Feeney, Mary; et al. (Allergy (Copenhagen), 2022)
Microbial metabolism of specific dietary components, such as fiber, contributes to the sophisticated inter‐kingdom dialogue in the gut that maintains a stable environment with important beneficial physiological, metabolic, and immunological effects on the host. Historical changes in fiber intake may be contributing to the increase of allergic and hypersensitivity disorders as fiber‐derived metabolites are evolutionarily hardwired into the molecular circuitry governing immune cell decision‐making processes. In this review, we highlight the importance of fiber as a dietary ingredient, its effects on the microbiome, its effects on immune regulation, the importance of appropriate timing of intervention to target any potential window of opportunity, and potential mechanisms for dietary fibers in the prevention and management of allergic diseases. In addition, we review the human studies examining fiber or prebiotic interventions on asthma and respiratory outcomes, allergic rhinitis, atopic dermatitis, and overall risk of atopic disorders. While exposures, interventions, and outcomes were too heterogeneous for meta‐analysis, there is significant potential for using fiber in targeted manipulations of the gut microbiome and its metabolic functions in promoting immune health.